Valuative tree - Favre Charles; Jonsson Mattias (Berlin Springer-Verlag, 2004)
This volume is devoted to a beautiful object, called the valuative tree and designed as a powerful tool for the study of singularities in two complex dimensions. Its intricate yet manageable structure can be analyzed by both algebraic and geometric means
Keywords: Valuative tree